2022-RA-1328-ESGO Comparison of prognostic risk scoring systems to predict outcomes in gynecologic oncology patients. (20th October 2022) - Vlachos, Dimitrios-Efthymios; Pergialiotis, Vasilis; Koutras, Antonis; Haidopoulos, Dimitris; Rodolakis, Alexandros; Thomakos, Nikolaos
Abstract : Introduction/Background: Surgery remains the main therapeutic module in many gynecologic malignancies. During the last decades, the operations have shifted to more radical and extensive procedures with multivisceral resections. This trend has come with increased complication rates, hospitalization, and healthcare costs. Multiple risk score systems have been proposed in order to identify high risk patients for adverse outcomes and Charlson comorbidity index (CCI) is widely accepted as highly accurate. This study compares CCI against Memorial Sloan Kettering-Frailty index (MSK-FI). Methodology: Retrospective analysis of 975 patients that have been operated in the Gynecologic Oncology Unit of our Department. The records of the patients were reviewed for risk factors and the department's readmissions and ICU admissions and deaths were retrieved from the complications database of the unit. Results: 26.3% of the patients had complications. Univariate analysis showed that older patient and patients of stage 3 and 4 and those with greater CCI had greater probability of complication. CCI but not MSK-FI, remained significant in multiple analysis. Twenty-two patients (2.3%) died. Multiple logistic regression showed that Greater age, CCI and MSK-FI were significantly associated with greater probability of dying. 1.7% of the patients were admitted to ICU. Greater age, CCI or MSK-FI were significantly associated with greater probability of being admitted to ICU. From multiple logistic regression emerged that only greater CCI was significantly associated with greater probability of being admitted to ICU. Median duration of hospitalization was 7 days (IQR: 5–10 days). Greater age, stage, CCI or MSK-FI were significantly associated with greater duration of hospitalization. When multiple linear regression was conducted it was found that CCI was significantly associated with greater duration of hospitalization. Conclusion: From our analysis MSK-FI is less accurate in identifying high risk patients for complications, ICU admission, increased hospitalization or complications' related death.